Production of microbial biosurfactants: Status quo of rhamnolipid and surfactin towards large‐scale production. Issue 7 (23rd May 2017) - Henkel, Marius; Geissler, Mareen; Weggenmann, Fabiola; Hausmann, Rudolf
Abstract: Surfactants are an important class of industrial chemicals. Nowadays oleochemical surfactants such as alkyl polyglycosides (APGs) become increasingly important. This trend towards the utilization of renewable resources continues and consumers increasingly demand for environmentally friendly products. Consequently, research in microbial surfactants has drastically increased in the last years. While for mannosylerythritol lipids and sophorolipids established industrial processes exist, an implementation of other microbially derived surfactants has not yet been achieved. Amongst these biosurfactants, rhamnolipids synthesized by Pseudomonas aeruginosa and surfactin produced by Bacillus subtilis are so far the most analyzed biosurfactants due to their exceptional properties and the concomitant possible applications. In this review, a general overview is given regarding the current status of biosurfactants and benefits attributed to these molecules. Furthermore, the most recent research approaches for both rhamnolipids and surfactin are presented with respect to possible methods for industrial processes and the occurring drawbacks and limitations researchers have to address and overcome. Abstract : Research on microbial biosurfactants has drastically increased in the last years. Rhamnolipids synthesized by Pseudomonas aeruginosa and surfactin produced by Bacillus subtilis are promising examples which are not yet established on a commercial large scale. In this review, a general overview is given regarding the current status and most recent research approaches for rhamnolipids and surfactin towards establishing industrial large‐scale production.